2022
DOI: 10.1186/s13104-022-06015-1
|View full text |Cite
|
Sign up to set email alerts
|

Overcrowded housing increases risk for COVID-19 mortality: an ecological study

Abstract: Objectives Overcrowded housing is a sociodemographic variable associated with increased infection and mortality rates from communicable diseases. It is not well understood if this association exists for COVID-19. Our objective was hence to determine the association between household overcrowding and risk of mortality from COVID-19, and this was done by performing bivariable and multivariable analyses using COVID-19 data from cities in Los Angeles County. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
(11 reference statements)
2
14
0
Order By: Relevance
“…Other studies showed that housing conditions, such as overcrowded housing, are an important risk factor for SARS-CoV-2 infection [ 1 , 26 ]. Household exposure can be a relevant risk factor for SARS-CoV-2 infection in patients who rarely leave their home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that housing conditions, such as overcrowded housing, are an important risk factor for SARS-CoV-2 infection [ 1 , 26 ]. Household exposure can be a relevant risk factor for SARS-CoV-2 infection in patients who rarely leave their home.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic, ecological, and politico-economic factors together with comorbidities have influenced the severity of Coronavirus disease 2019 (COVID-19) worldwide [ 1 ]. Among others, this pandemic has also raised health concerns related to people with multiple sclerosis (PwMS) in the acute phase of the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the poor housing conditions, particularly for low-income and minority ethnic populations, have become vulnerable to COVID-19 spread and infection [ 150 ]. Several studies have linked poor housing conditions with worse health outcomes and infectious diseases of COVID-19 spread [ 151 , 152 ]. Ahmad et al conducted a cross-sectional analysis of county-level data in US among households with poor housing conditions, including conditions such as overcrowding, high housing cost, incomplete kitchen facilities, or incomplete plumbing facilities [ 151 ].…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Overcrowding and poor plumbing may lead to recurrent exposure and potentially a higher viral inoculum, which had been connected to worse COVID-19 clinical outcomes. Varshney and Adalbert conducted bivariable and multivariable analyses using COVID-19 data from cities in Los Angeles County to determine the association between household overcrowding and risk of mortality from COVID-19 [ 152 ]. The bivariate regression revealed that overcrowded households were positively associated with COVID-19 deaths (standardized β = 0.863, p < 0.001).…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Conventional methods, such as stepwise selection, are usually applied for variable selection in diseases 14 18 . However, they have the disadvantage of overfitting 19 .…”
Section: Introductionmentioning
confidence: 99%